SCHOOL BASED ASSESSMENT IN THE VOCATIONAL COURSES AND THE UNIVERSAL BASIC EDUCATION (UBE) - OSEIWU ALI, DR. (MRS) HASSANA (IJRDO - Journal of Social Science and Humanities Research, 2016)
The study was designed to determine whether or not the school based assessment is preferred by the students/teachers in the UBE programme, in Rivers State. A simple random sample of 200 students was selected from 16 Junior Secondary Schools 3 with a total population of 2,439, while 100 teachers were also selected randomly from 445 teachers. The mean and standard deviation, t – test and ANOVA was used for the analysis. The major findings point to the fact that the students preferred the school based assessment than the onetime assessment by the ministry of education, while the teachers also see it as a welcome ideal, this could be trace to genuine fact that vocational courses are more practical in nature and required weekly, if not daily practical assessment. And also there is no significant difference between the attitude of students and teachers toward school based assessment, but there was a significant difference between the attitudes of students towards school assessment in favour of male students. It is recommended that the federal government through the federal ministry of education and the examination bodies (WAEC, NABTECH and NECO) in Nigeria should liaised and agree on increasing the percentage of the score ascribe to school based evaluation in addition to examination bodies score and that Practical instruments should be provided for the students to boost interest in learning and acquisition of skills, to gain the needed knowledge for independent life after graduation